Let $\lambda$ be a nonzero real constant. Find all functions $f,g: \Bbb R \rightarrow \Bbb R$ that satisfy the functional equation $f(x+y)+g(x−y)=\lambda f(x)g(y)$.

I try this :

Let $y=0$ in the equation to get $f(x)+g(x)=\lambda f(x)g(0)$

Here We have two cases:

  1. $g(0)=0$ here $f(x)=-g(x)$

  2. $g(0) \neq 0$ here $g(x)=\beta f(x)$ , $\beta = g(0)\lambda-1$

Is this true? And if this true how I can complete the the solution especially in case two?


Just the idea, you need to calculate them yourself.

First, $y=0$.

$g(x) = (\lambda g(0) - 1)f(x) $, to be short, there is a constant $C$, that

$$g(x) = Cf(x)$$


$$f(x+y) + Cf(x-y) = \lambda C f(x)f(y)$$

take $x=y$.

$$f(2x) = \lambda C f(x)^2 - Cf(0)$$

take $x=2y$

$f(3y) + f(y) = \lambda C f(2y) f(y) = \lambda C(\lambda C f(y)^2 - Cf(0))f(y) = (\lambda C)^2 f(y)^3 - \lambda C^2f(0)f(y)$

$$f(3y) = (\lambda C)^2 f^3(y) - (1 + \lambda C^2 f(0))f(y)$$

take $x = 3y$

$$f(4y) = \lambda C f(3y)f(y) - Cf(2y)$$


$$f(4y) = \lambda C f(2y)^2 - Cf(0)$$

solve this , you can get

$$(-\lambda - \lambda C +\lambda^2 C^2 f(0)) f(x)^2 = (\lambda C^2 - C - 1)f(0)$$

then it is easy to observe that if the coefficient of left side is not zero, then $f$ is a constant.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.